Application of a low‐cost NDIR sensor module for continuous measurements of in situ soil CO2 concentration. Issue 5 (21st June 2020) - Heger, Adrian; Kleinschmidt, Volker; Gröngröft, Alexander; Kutzbach, Lars; Eschenbach, Annette
Abstract: We tested the performance of a newly developed CO2 probe, K33SOIL [based on the sensor module K33 (Senseair, Sweden)], under harsh temperature and humidity conditions in a laboratory experiment. The K33SOIL, competed well (RMSE = 0.032% CO2 ) with the often used GMP343 (Vaisala, Finland) in precision and accuracy. A field experiment showed that the K33SOIL is also suitable for in situ applications. Thus, the K33SOIL is a valuable and cost‐efficient tool for measurement of soil CO2 concentration.